STUDY LITERATURE OF THE EFFECTIVENESS OF AEROBIC GYMNOW TO BLOOD GLUCOSE LEVELS IN PATIENTS DIABETES MELLITUS TYPE 2 (STUDI LITERATUR EFEKTIVITAS SENAM AEROBIK TERHADAP KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2) - Ilham, Radiah; Ramlah, Ramlah; Sudirman, Sudirman (Journal of Applied Health Management and Technology, 2021)
Diabetes mellitus is a type of non-communicable disease that can cause high morbidity and mortality. This disease is not a new disease, it's just that it doesn't get enough attention in the community, especially those who have a high risk of suffering from the disease. The purpose of this literature study is to identify recommendations about the effectiveness of aerobic exercise on blood glucose levels in type 2 Diabetes Mellitus patients. This literature search was conducted to find articles that fit the topic through the Google Scholar database using keywords or Keyword aerobics "OR" blood. sugar level "AND" type 2 diabetes mellitus . A Google Scholar search was carried out for screening years (2010-2020) and using the phrase " aerobics blood sugar level ". Based on the results of a literature search from 17 articles obtained, there were 10 articles that met the inclusion criteria and through a review it was found that 8 out of 10 journal articles obtained were 75% of the effectiveness of aerobic exercise on blood glucose levels in type 2 diabetes mellitus patients. And 25% experienced an increase in blood glucose levels after doing aerobic exercise in other words, it was found that aerobic exercise was not effective against blood glucose levels in patients with type 2 diabetes mellitus. aerobics. Keywords : Aerobic Exercise, Blood Glucose Levels, Diabetes Mellitus Type 2